The effectiveness of special endurance exercises on diminishing the angular kinetic energy of body parts when re-performing front and back shots in squash - Qaddouri, Yaser Wajih; Salman, Mohammed Ghazi (International Journal of Psychosocial Rehabilitation, 2020)
Squash is considered one of the games that require great physical effort through the continuous movement speed that the squash player needs while he moves to perform the front and back shots , the problem of research lies through a previous study in the use of an EMG device for working muscles when performing the front and back shots. During the previous study, the researcher recommended the use of special endurance exercises to develop players as a result of a decrease in the value of the electrical signal when the player performs large repetitions during play. The two researchers believe that this weakness in the player’s own endurance abilities (endurance of speed and strength) led to that decline and directed in this study to knowing the effect of special endurance exercises on decreasing the angular kinetic energy of body parts when re-performing the front and back shots of the youth national squash team. The most important objectives of the research: To identify the effect of the decrease in the angular kinetic energy of some parts of the body, and its reflection on the speed of performing back and front straight shots in squash. The researchers concluded that special endurance exercises led to a delay in the decrease in the angular kinetic energy of body parts when repeated front and back strokes in squash.